Combination of ankylosing spondylitis with combined autoinflammatory skin lesions (clinical observation and literature review) - D. A. Dibrov; T. V. Korotaeva; S. O. Krasnenko; M. M. Urumova; L. S. Kruglova; A. M. Lila (Современная ревматология, 2021)
We present a clinical case of combination of axial spondyloarthritis (axSpA) and chronic recurrent skin lesions in the form of acne conglobata, hidradenitis suppurativa (HS) with fistulous tracts formation. During the diagnostic search, the following diseases were considered: HS, SAPHO syndrome (synovitis, acne, pustulosis, hyperostosis, osteitis), PASS syndrome (pyoderma gangrenosum, acne, ankylosing spondylitis, HS). The choice of therapy in this patient and the possibility of using biologic disease-modifying antirheumatic drugs for axSpa and concomitant autoinflammatory skin process are discussed.